FREQUENCY OF OCCURRENCE OF CHRONIC VIRAL HEPATITIS AMONG THE POPULATION OF THE REPUBLIC OF AZERBAIJAN ACCORDING TO THE DATA ON CIRCULATION - Farajova, N.A.; Makhmudova, K.J. (World of Medicine and Biology, 2023)
1,611 people who applied to the medical center “Medikus Clinic” in Baku were examined, 836 of them were men and 775 women. Verification of viral hepatitis B and viral hepatitis C was carried out based on the determination of the hepatitis B virus surface antigen using enzyme immunoassay and hepatitis C virus by polymerase chain reaction on the immunochemical analyzer Beckman Coulter Unicel DXi 800. Of the total number of examined patients, hepatitis B was detected in 642 patients (39.85 %), of which 24.8 % were men and 15.02 % were women. The analysis of the data revealed a high incidence of the disease in people under 40 years of age with a sharp decrease in the indicator after 40 years and a minimum value after 60. In patients with hepatitis C without regional differences, an increase in the incidence of the disease was detected in the age range from 30 to 60 years. In the 60≤ group, there was a decline in the disease in men. It was found that the patients were mainly concentrated in Baku, then in the regions of Azerbaijan and in Sumgait. Unlike age, the male sex has always retained its importance as a risk factor. Chronic types of viral hepatitis B and viral hepatitis C were more common in people of working age.
Keywords: chronic hepatitis B; chronic hepatitis C; age dynamics; men; women